Is orbital volume associated with eyeball and visual cortex volume in humans? - Pearce, E; Bridge, H (2013)
BACKGROUND: In humans orbital volume increases linearly with absolute latitude. Scaling across mammals between visual system components suggests that these larger orbits should translate into larger eyes and visual cortices in high latitude humans. Larger eyes at high latitudes may be required to maintain adequate visual acuity and enhance visual sensitivity under lower light levels. AIM: To test the assumption that orbital volume can accurately index eyeball and visual cortex volumes specifically in humans. SUBJECTS AND METHODS: Structural Magnetic Resonance Imaging (MRI) techniques are employed to measure eye and orbit (n = 88) and brain and visual cortex (n = 99) volumes in living humans. Facial dimensions and foramen magnum area (a proxy for body mass) were also measured. RESULTS: A significant positive linear relationship was found between (i) orbital and eyeball volumes, (ii) eyeball and visual cortex grey matter volumes and (iii) different visual cortical areas, independently of overall brain volume. CONCLUSION: In humans the components of the visual system scale from orbit to eye to visual cortex volume independently of overall brain size. These findings indicate that orbit volume can index eye and visual cortex volume in humans, suggesting that larger high latitude orbits do translate into larger visual cortices.